Pengaruh Kualitas Pelayanan dan Harga terhadap Loyalitas Pelanggan dengan Variabel Kepuasan Konsumen sebagai Variabel Intervening pada J&T Express (Studi pada J&T Express di Kota Sidoarjo) - Ayu Ranjani, Herturasya; Prabowo, Budi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
J&T is a goods delivery company that is experiencing development along with market growth. This research to analyze the relationship between quality and price on loyalty with satisfaction as an interverning variable. The theory used in this research is marketing theory. The method in this research is quantitative with the population being J&T Sidoarjo consumers, while the sample is 100 J&T consumers using the Slovin method and random sampling. Data processing analysis was carried out using path analysis. Data collection was carried out through a form distributed by the author to J&T consumers. The research results show that satisfaction mediates J&T Express service quality on loyalty. Satisfaction mediates J&T Express Prices on Loyalty. Satisfaction mediates Price on Customer Loyalty. Satisfaction has an effect on loyalty, in contrast to price it has no effect on consumer loyalty.